Experimental design to optimization of beta cyclodextrin production from ungelatinized sago starch - Rauf, Zulfikri A.; Ilias, Rosli Md.; Mahadi, Nor Muhammad; Hassan, Osman (Springer Berlin / Heidelberg, 2008)
The aim of this study is to produce beta cyclodextrin (Î²-CD) from ungelatinized, but annealed (65 Â°C) sago starch using cyclodextrin glucosyltransferase (CGTase). The optimization processes were conducted at three stages using Response Surface Methodology. Preliminary data have shown that the three (3) highest points for each of the studied parameters were pH, concentration of sago starch and enzyme, and also agitation. In the second stage, two level full factorial design (2n FFD) was applied to determine the significant parameters affecting the production of Î²-cyclodextrin. Statistical analyses showed that pH, enzyme and sago starch concentration were the significant parameters. The final stage of optimization involved the use of Central Composite Design to determine and predict the optimum yield of Î²-cyclodextrin. The optimum condition for production cyclodextrin was at pH 8.62 (Glycineâ€“NaOH buffer 0.05 M), 0.65% v/v sago starch and 15% w/v enzyme concentration, where 8.43 g Î²-cyclodextrin/L was produced after 4 h of reaction.